2021
DOI: 10.3390/jcm10173908
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Adolescents with Concurrent Substance Use Disorder and Attention-Deficit/Hyperactivity Disorder: A Systematic Review

Abstract: Childhood attention-deficit/hyperactivity disorder (ADHD) is a risk factor for the development of substance abuse and substance use disorders (SUD) in adolescence and (early) adulthood. ADHD and SUD also frequently co-occur in treatment-seeking adolescents, which complicates diagnosis and treatment, and is associated with poor treatment outcomes. In this study, we provide a systematic review of controlled studies on the effectiveness of pharmacological, psychosocial, and complementary treatments of ADHD in ado… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 82 publications
0
5
0
2
Order By: Relevance
“…Wilens et al found an overall reduced risk of developing any SUD in later life (mean OR = 1.9) in patients who had received stimulant treatment than those who had not (50). In line with these findings, reviews suggest that stimulant treatment of childhood ADHD may have a preventive effect on the development of SUD in adolescence and early adulthood (23). More specifically, Groenman et al described that stimulant treatment at an early stage, high dose, and longer duration were associated with a reduced risk of SUD in adolescence (51,52).…”
Section: Co-occurring Mental Disorders and Phenomena Of Substance Use...mentioning
confidence: 92%
See 4 more Smart Citations
“…Wilens et al found an overall reduced risk of developing any SUD in later life (mean OR = 1.9) in patients who had received stimulant treatment than those who had not (50). In line with these findings, reviews suggest that stimulant treatment of childhood ADHD may have a preventive effect on the development of SUD in adolescence and early adulthood (23). More specifically, Groenman et al described that stimulant treatment at an early stage, high dose, and longer duration were associated with a reduced risk of SUD in adolescence (51,52).…”
Section: Co-occurring Mental Disorders and Phenomena Of Substance Use...mentioning
confidence: 92%
“…The link between childhood attention-deficit/hyperactivity disorder (ADHD) and early SUD in youth and young adults has been well-established ( 23 , 24 ). Skoglund et al ( 25 ) found that not only the affected but also relatives of individuals with ADHD are more likely to develop SUDs ( 25 ).…”
Section: Co-occurring Mental Disorders and Phenomena Of Substance Use...mentioning
confidence: 99%
See 3 more Smart Citations